2017
DOI: 10.1002/term.2506
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal barrier integrity and inflammatory bowel disease: Stem cell‐based approaches to regenerate the barrier

Abstract: Disruption of normal barrier function is a fundamental factor in the pathogenesis of inflammatory bowel disease, which includes increased epithelial cell death, modified mucus configuration, altered expression and distribution of tight junction proteins, along with a decreased expression of antimicrobial peptides. Inflammatory bowel disease is associated with life-long morbidity for affected patients, and both the incidence and prevalence is increasing globally, resulting in substantial economic strain for soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 137 publications
0
41
0
Order By: Relevance
“…The gastrointestinal tract is one of the target organs of I/R injury and is often described as the central organ of surgical stress and the initiating organ of multiple organ failure (24). The intestinal mucosa is rich in blood supply to ensure the absorption of nutrients and the maintenance of normal barrier function (25). Due to certain characteristics of intestinal villus oxygen exchange, including that the oxygen tension at the tip of villus is lower than that of the artery, cells have a high sensitivity to hypoxia and ischemia (26).…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal tract is one of the target organs of I/R injury and is often described as the central organ of surgical stress and the initiating organ of multiple organ failure (24). The intestinal mucosa is rich in blood supply to ensure the absorption of nutrients and the maintenance of normal barrier function (25). Due to certain characteristics of intestinal villus oxygen exchange, including that the oxygen tension at the tip of villus is lower than that of the artery, cells have a high sensitivity to hypoxia and ischemia (26).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is mounting for endothelial impairment contributing to the onset, progression and recovery from inflammatory injury. 135 , 136 Of particular interest, EPCs, derived from bone marrow hematopoietic stem cells, have the capability to migrate to the site of endothelial damage through the peripheral circulation. 137 Boltin and colleagues 137 studied patients with CD in varying stages of disease activity assessed using the CDAI.…”
Section: Pluripotent Progenitor and Stem Cells As Surrogate Prognostimentioning
confidence: 99%
“…Multiple studies have showed that inflammatory bowel disease (IBD) is a disorder of dysregulation by inflammation accompanied by impaired intestinal barrier function, which is an vital event in treatment of IBD [ 1 , 2 ]. The local inflammatory reaction is involved in the recruitment of various inflammatory cells and secretion of cytokines, including matrix metalloproteinases (MMPs), IL-1 β , and IL-6, which have a critical role in regulation of intestinal barrier function, thereby resulting in aggravating development of IBD.…”
Section: Introductionmentioning
confidence: 99%